A soft tick vector of Babesia sp. YLG in Yellow-legged gull (Larus michahellis) nests - Bonsergent, Claire; Vittecoq, Marion; Leray, Carole; Jouglin, Maggy; Buysse, Marie; McCoy, Karen D.; Malandrin, Laurence (Peer Community Journal, 2023)

(untitled)
Abstract Babesia sp. YLG has recently been described in Yellow-legged gull (Larus michahellis) chicks and belongs to the Peircei clade in the new classification of Piroplasms. Here, we studied Babesia sp. YLG vectorial transmission by ticks in the simplified environment of a single seabird breeding colony where the Yellow-legged gull is the sole vertebrate host, Ornithodoros maritimus (syn. Alectorobius maritimus) the sole tick species, and Babesia sp. YLG is the only blood parasite species detected in chicks of the colony. We collected ticks over four years, maintained certain individuals through moulting or oviposition, and dissected fresh ticks to isolate different organs and test for the presence of the parasite using molecular assays. We report the first strong evidence of a Piroplasmidae transmitted by a soft tick. Indeed, Babesia sp. YLG DNA was detected in the salivary glands of nymphs, females and males, a necessary organ to infect for transmission to a new vertebrate host. Parasite DNA was also found in tick ovaries, which could indicate possible transovarial transmission. Our detection of Babesia sp. YLG DNA in several male testes and in endospermatophores, and notably in a parasite-free female (uninfected ovaries and salivary glands), raise the interesting possibility of sexual transmission from infected males to uninfected females. Future work in this system will now need to focus on the degree to which the parasite can be maintained locally by ticks and the epidemiological consequences of infection for both O. maritimus and its avian host.